Aplikasi Berbasis Web untuk Persediaan Kain Tekstil dengan QRIS untuk PT. Mulya Jaya Kab. Majalaya - Kahla Modwen Lena, Yasmine; Gde Agung, Anak Agung; Suprihatin, Eti (eProceedings of Applied Science, 2024)
Effectiveness of QRIS Implementation for inventory andsales in improving inventory and sales at PTMulya Jaya. This research aims to find outhow the QRIS method can improve the inventory systemat PT Mulya Jaya. The type of research used isqualitative research method, which is a form of research thataims to provide an overview by exploringdata and facts in the field, in order to get factual information from the research location in the form of written words or facts.factual information from the research location in the form of written or oral words from sources. Data collection techniquestechniques used are observation, interview and documentation.documentation. The results showed that the application ofQRIS has been able to improve the system, making it easy to check stock inventory and sales.check the stock of inventory and sales. Achievement oftargets where data from system results, inventory and salesusing QRIS already looks effective. Keywords - Inventory, Sales, QRIS